Консули європейських країн у Миколаєві (друга половина ХІХ – початок ХХ ст.) - Вовчук, Л. (Міжнародні зв’язки України: наукові пошуки і знахідки, 2017)
У статті розглянуто становлення консульських установ європейських держав у Миколаєві та роль іноземних консульських представників
у житті міста упродовж другої половини ХІХ — початку ХХ століття.
Піклуючись про інтереси власної держави та громадян, вони водночас
сприяли розвитку торгівлі, комерційної діяльності, піднесенню банків і
лікарень міста, значний внесок зробили у піднесення освіти, газетної
справи, науки, мистецтва, спорту, духовного життя громадян та власне
у розбудову південноукраїнських міст. An integral part of modern Ukrainian historical science is to study
consular missions on the territory of modern Ukraine, which, unfortunately, for
many years has not caused interest of scholars. This article examines the
formation of European states’ consular offices in Mykolayiv and the role of
foreign consular representatives in the city during the second half of the
nineteenth and early twentieth centuries. Taking care of the interests of their
own state and citizens, they simultaneously contributed to the development of
trade, commercial activity, the rise of banks and hospitals in the city, made a
significant contribution to the progression of education, newspapers, science,
art, sports, spiritual life of citizens and, in fact, to the development of southern
Ukrainian cities.